(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2022)
In modern times, the process of tattooing has withdrawn a lot of attention Investigators and consultants in the field of tattooing premeditated its significance regarding different perspectives such as sociological speculative grounds besides social factors effects on gender, one’s social identity, age group, sub-cultures regarding urban and ruler areas, occupational status. In this study, socio-cultural impacts and sociological implication perspectives of tattooing among young modern women in Basra were examined. The main purpose of this study is to find the root causes that influence young modern women to undergo tattoo embeddedness. Another purpose of this study is to find any social-cultural factors that are influencing or discouraging tattooing among young women and how these marks are helpful in communication as well as having a unique identity. This research was conducted in two parts reviewing literature review and conducting in-depth interviews. The inductive research approach was used for this purpose. The non-probability technique was used for sample selection which was five young college-going women. From the results, it was concluded that tattoos are becoming a powerful tool for individual self-expression and presentation of who they are. Inscribing tattoos on the body represents a person as a figurative symbol. Love, freedom, imagination, and idealism are a form of a few self-expressions that women like to represent through their inscribing bodies.